Dose- and Time-Dependent Efficacy of Topical Hydroquinone in Establishing a C57BL/6 Mouse Model of Vitiligo - Benedikta Lauda; Nurrachmat Mulianto; Endra Yustin Ellistasari; Muhammad Eko Irawanto (HM Publisher, 2026)
Background: Vitiligo is a complex autoimmune depigmenting disorder driven by melanocyte-specific CD8+ T cells, oxidative stress, and genetic susceptibility. The lack of standardized, accessible animal models that recapitulate these pathways hinders therapeutic development. This study aimed to systematically optimize and validate a chemically-induced vitiligo model in C57BL/6 mice. Methods: Eighty (80) male C57BL/6 mice were randomized into ten groups (n=8/group). Experimental groups received once-daily topical applications of hydroquinone (HQ) at 2.5%, 5%, or 10%, or monobenzone (MBZ) at 40% for 8 or 16 days. Vehicle-treated mice served as controls. Efficacy was assessed via quantitative histopathology (Masson-Fontana staining for melanin area), biomolecular assays for oxidative stress (Malondialdehyde [MDA] and Superoxide Dismutase [SOD]), and RT-qPCR for melanogenesis-related (Tyr) and inflammation-related (Tnf) gene expression. Results: A clear dose- and time-dependent depigmentation was observed. The 10% HQ 16-day protocol was maximally effective, inducing a profound reduction in epidermal melanin area (0.06 ± 0.02) compared to 16-day controls (0.40 ± 0.04; p < 0.001). This histopathological finding was significantly correlated with severe cutaneous oxidative stress, evidenced by a 3.75-fold increase in MDA (p < 0.001) and a 50% reduction in SOD activity (p < 0.001) versus controls. Furthermore, this regimen caused a potent suppression of Tyr expression (0.15-fold change; p < 0.001) and a significant upregulation of the pro-inflammatory cytokine Tnf (3.8-fold change; p < 0.001). Conclusion: The 16-day topical application of 10% hydroquinone is a reliable, rapid, and highly reproducible protocol for inducing vitiligo-like depigmentation in C57BL/6 mice. This model successfully recapitulates key pathophysiological pillars of human vitiligo, including melanocytotoxicity, profound oxidative stress, and a pro-inflammatory cutaneous environment, establishing it as a valuable platform for preclinical therapeutic screening.